2017
DOI: 10.3310/hta21040
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial and economic analysis of an internet-based weight management programme: POWeR+ (Positive Online Weight Reduction)

Abstract: BackgroundBehavioural counselling with intensive follow-up for obesity is effective, but in resource-constrained primary care settings briefer approaches are needed.ObjectivesTo estimate the clinical effectiveness and cost-effectiveness of an internet-based behavioural intervention with regular face-to-face or remote support in primary care, compared with brief advice.DesignIndividually randomised three-arm parallel trial with health economic evaluation and nested qualitative interviews.SettingPrimary care gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
151
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(153 citation statements)
references
References 48 publications
1
151
0
Order By: Relevance
“…26 Previous studies have also shown that weight management programmes in adults have successfully shown a reduction of 1 kg/m 2 in BMI. Our study suggests that if this was to be achieved in women with overweight or obesity prior to pregnancy , 27 this would reduce the risk of increased infant adiposity. It is therefore plausible that the effect sizes found are meaningful at a population level.…”
Section: Discussionmentioning
confidence: 86%
“…26 Previous studies have also shown that weight management programmes in adults have successfully shown a reduction of 1 kg/m 2 in BMI. Our study suggests that if this was to be achieved in women with overweight or obesity prior to pregnancy , 27 this would reduce the risk of increased infant adiposity. It is therefore plausible that the effect sizes found are meaningful at a population level.…”
Section: Discussionmentioning
confidence: 86%
“…Four additional papers were identified from included RCTs. In all, 33 papers met our inclusion criteria 17–49…”
Section: Resultsmentioning
confidence: 99%
“…Although no included papers provided qualitative data from those who had been invited to join a programme, but had declined to take part at recruitment stage, some papers reported including participants who had not fully engaged with programme activities (being described as ‘low users’; ‘quitters’ or ‘drop outs’) 17 24 25 36…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations